2013
DOI: 10.2478/pjct-2013-0037
|View full text |Cite
|
Sign up to set email alerts
|

The unconventional single stage hydrolysis of potato starch

Abstract: Enzymatic depolymerisation of starch to glucose or maltose is carried out by starch-degrading amylases during a two-stage hydrolysis: liquefaction using bacterial α-amylase followed by saccharifi cation with glucogenic (fungal amylase) or maltogenic (fungal or bacterial) amylases. As a rule, these enzymes are applied separately, following the recommendations concerning their action provided by the enzyme manufacturers. The study presents our attempts to determine the reaction conditions for a simultaneous acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…A shorter reaction time for hydrolysis (30-48 h) can be achieved using glucoamylase and debranching enzymes (Hii et al, 2012). The conventional two-stage hydrolysis has certain technological disadvantages, such as different temperature and pH requirements, increasing energy consumption, and auxiliary materials used in hydrolysate purification (Słomińska et al, 2013).…”
Section: Single-stage Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…A shorter reaction time for hydrolysis (30-48 h) can be achieved using glucoamylase and debranching enzymes (Hii et al, 2012). The conventional two-stage hydrolysis has certain technological disadvantages, such as different temperature and pH requirements, increasing energy consumption, and auxiliary materials used in hydrolysate purification (Słomińska et al, 2013).…”
Section: Single-stage Hydrolysismentioning
confidence: 99%
“…The aforementioned inconveniences can be overcome using a novel single-stage hydrolysis, facilitating shortened hydrolysis time, simplified hydrolysis process, improved enzymatic efficiency and starch conversion. Słomińska et al (2013) established a simultaneous reaction system of liquefying and saccharifying enzymes on pretreated potato starch. During the single-stage starch hydrolysis, the most desired results were obtained at 80 • C (DE 51.6) and 60 • C (DE 96) for the maltose hydrolysate and glucose hydrolysate, respectively.…”
Section: Single-stage Hydrolysismentioning
confidence: 99%
“…Untuk mengatur pH hidrolisis dilakukan penambahan HCl 0,1 mol L -1 (Collares et al, 2012). Enzim pertama yang digunakan untuk proses likuifikasi ialah α-amilase Liquozyme ® Supra (Novozyme) yang aktivitasnya 135 KNU/g (Kilo Novo Unit/g) dan diaplikasikan pada pH rendah (5,2-5,6), suhu 90-95 o C selama 90 menit (Słomińska et al, 2013). Dosis enzim yang digunakan untuk likuifikasi adalah 0,127 KNU/g pati dalam keadaan kering padat.…”
Section: Penyiapan Media Fermentasi Nataunclassified
“…Only few studies did combine both stages to hydrolyze different substrates such as cassava [ 17 ], potato starch [ 18 ] and wheat starch [ 19 ]. All these studies showed the convenience of the single-step method for starch hydrolysis since it could facilitate a more efficient use of energy and time, as well as a higher efficiency of starch conversion.…”
Section: Introductionmentioning
confidence: 99%